Eight Cases Found to Have False-positive SARS-CoV-2 Tests after Admission to a COVID-19 Ward - SATO, Yuki; NAKAE, Mami; NIRASAWA, Shinya; KOBAYASHI, Ryo; KURONUMA, Koji; TAKAHASHI, Satoshi; MURAI, Ryosei; FUJIYA, Yoshihiro (Japanese Journal of Infection Prevention and Control, 2024)
There are multiple testing methods for SARS-CoV-2 used to definitively diagnose COVID-19, but the test sensitivity and specificity are not 100%.Of the 421 people who were diagnosed with COVID-19 and admitted to the dedicated ward between January 1 and December 31, 2021, we experienced eight false-positive cases. Five patients were hospitalized or tested for preoperative screening purposes, but all were asymptomatic and had low pretest probability. All eight cases had no history of behavior or contact that could lead to infection, and the epidemiological link was low; therefore, the test results had to be interpreted with caution.Tests have limitations, and it is inevitable that there will be a certain probability of false positives. For cases in which a false-positive is suspected on the basis of the purpose of the test or clinical symptoms, it is necessary to collect the sample again and consider retesting.